Variation in the ace gene in elite Polish football players - Cieszczyk, P.; Leonska-Duniec, A.; Maciejewska-Skrendo, A.; Sawczuk, M.; Leznicka, K.; Contro, V.; Trybek, G.; Lulinska-Kuklik, E. (Human Movement, 2016)
A common polymorphism in the angiotensin converting enzyme I gene (the ACE I/D variant) represents one of the first characterized and the most widely studied genetic variants in the context of elite athletes status and performance related traits. The aim of the study was to determine the genotype and allele distribution of the allele and genotype of the ACE gene in Polish male football players. Methods. The total of 106 Polish male professional football players were recruited. They were divided into groups according to the position in the field: forwards, defenders, midfielders, and goalkeepers. For controls, samples were prepared with 115 unrelated volunteers. DNA was extracted from the buccal cells donated by the subjects, and the PCR amplification of the polymorphic region of the ACE gene containing either the insertion (I) or deletion (D) fragment was performed. Results. The genotype distribution and allele frequencies among all football players did not differ significantly when compared with sedentary control individuals (p = 0.887, p = 0.999, respectively). Likewise, the analysis of forwards, defenders, midfielders, and goalkeepers revealed no significant differences in either ACE genotype or allele frequencies. Conclusions. We did not provide evidence for difference of variation of the ACE I/D polymorphism between Polish football players and controls, as we did not obtain any statistically significantly higher frequency of either of the analysed alleles (I and D) or genotypes (DD, ID, and II) in the studied subgroups. It may be suspected that harbouring of I/D allelic variants of the ACE gene neither decreases nor increases the probability of being a professional football player in Poland.